2016
DOI: 10.1038/ncomms13431
|View full text |Cite
|
Sign up to set email alerts
|

Borane catalysed ring opening and closing cascades of furans leading to silicon functionalized synthetic intermediates

Abstract: The conversion of renewable biomass resources to synthetically valuable chemicals is highly desirable, but remains a formidable challenge in regards to the substrate scope and reaction conditions. Here we present the development of tris(pentafluorophenyl)borane–catalysed conversion of furans via ring-opening and closing cascade processes to afford silicon-functionalized synthetic chemicals under transition metal-free conditions. The furan ring-opening with hydrosilanes is highly efficient (TON up to 2,000) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 52 publications
0
45
0
3
Order By: Relevance
“…In 1997, Pietruzska reported a protocol to convert tartrate‐bound boronic esters 69 to the corresponding cyclopropanols in modest to good yields and good enantiomeric excesses (Scheme a) . In 2016, Chang and co‐workers showed that cyclopropylsilane 71 could undergo a Tamao–Fleming oxidation to deliver the corresponding cyclopropanol 72 (Scheme b) …”
Section: Synthesis Of Homoenolatesmentioning
confidence: 99%
“…In 1997, Pietruzska reported a protocol to convert tartrate‐bound boronic esters 69 to the corresponding cyclopropanols in modest to good yields and good enantiomeric excesses (Scheme a) . In 2016, Chang and co‐workers showed that cyclopropylsilane 71 could undergo a Tamao–Fleming oxidation to deliver the corresponding cyclopropanol 72 (Scheme b) …”
Section: Synthesis Of Homoenolatesmentioning
confidence: 99%
“…In 2016, Chang and co‐workers discovered the borane‐catalyzed hydrosilylative ring opening and closing cascades of furans, which enabled the chemoselective synthesis of α‐silyloxy homoallylsilanes and silylated cyclopropanes with excellent chemo‐, regio‐, and stereoselectivities . Opening of the furan ring with hydrosilanes was highly efficient (TON up to 2000) at 25 °C, forming a new sp 3 ‐C−Si bond α to the oxygen atom.…”
Section: Hydrosilylative Reduction Of Four‐ Five‐ and Six‐membered mentioning
confidence: 99%
“…[7] Recently,w ereported aB (C 6 F 5 ) 3 -catalyzed cascade conversion of furans providing silicon-functionalized compounds, in which ahomoallylic intermediate was assumed to undergo ac oncerted S N 2'-type ring-closing process to furnish cyclopropanes with exclusive trans-selectivity (Scheme 1b). [8] GagnØ and co-workers found that B(C 6 F 5 ) 3 promotes areductive cyclization of silyl-protected unsaturated polyols to give cyclopropanes and cyclopentanes depending on the substituents adjacent to the alkenyl moiety (Scheme 1c). [9] Unlike in our previous work, [8] GagnØ suggested as tepwise pathway involving an intramolecular attack of an eighboring alkenyl group at the activated CÀObond of the silaoxonium ion.…”
mentioning
confidence: 99%